STUDI KORELASI ANTARA CARING PERAWAT DENGAN KEPUASAN KLIEN YANG MENJALANI PERAWATAN - Nova Arikhman (Jurnal Ipteks Terapan, 2011)
The purpose of this research is to find out relationship of client’s perception about the nurse’s caring behavior with client’s satisfaction at the Endocrinological Department of Bukittinggi National Stroke Hospital.  The research is descriptive correlation by using cross-sectional approach.  The research population consist of all patient who cared, totaling 64 respondents and all of them are taken as research respondent (total sampling).  To collect data, the researcher uses questioners. The statistical analysis, indicates that there is significant the relationship of the nurse’s caring behavior with client’s satisfaction.  On the based of the research findings, it is recommended to nurse’s to be able, to give the service by using the caring modality and polite request like keeping and eye on all patient all the time.